Vitamin B-12 Deficiency in Children Is Associated with Grade Repetition and School Absenteeism, Independent of Folate, Iron, Zinc, or Vitamin A Status Biomarkers. Issue 7 (13th May 2015) - Duong, Minh-Cam; Mora-Plazas, Mercedes; Marín, Constanza; Villamor, Eduardo
Abstract: Background: Micronutrients are essential to neurocognitive development; yet their role in educational outcomes is unclear. Objective: We examined the associations of micronutrient status biomarkers with the risk of grade repetition and rates of school absenteeism in a cohort of school children. Methods: We recruited 3156 children aged 5–12 y from public schools in Bogota, Colombia. Circulating ferritin, hemoglobin, zinc, vitamin A, and vitamin B-12; erythrocyte folate; and mean corpuscular volume (MCV) were measured in blood samples obtained at the beginning of the year. Absenteeism was recorded weekly during the school year, and grade repetition was determined the next year. Risk ratios for grade repetition and rate ratios for absenteeism were estimated by categories of micronutrient status indicators with use of Poisson regression, adjusting for potential confounders. Results: The risk of grade repetition was 4.9%, and the absenteeism rate was 3.8 d per child-year of observation. Vitamin B-12 deficiency (<148 pmol/L) was associated with an adjusted 2.36-fold greater risk of grade repetition (95% CI: 1.03, 5.41; P = 0.04) compared with plasma concentrations ≥148 pmol/L. Other micronutrients were not related to grade repetition. Vitamin B-12 deficiency was also associated with school absenteeism rates. Compared with children with plasma vitamin B-12 concentrations ≥148 pmol/L, vitamin B-12-deficient children had a 1.89-times higher adjusted rate (95% CI: 1.53, 2.34; P < 0.0001). Anemia was related to a 72% higher rate (95% CI: 48%, 99%; P < 0.0001), whereas every 5-fL difference in MCV was associated with a 7% lower adjusted rate (95% CI: 4%, 10%; P < 0.0001). Conclusions: Vitamin B-12 deficiency was associated with risk of grade repetition and school absenteeism rates in school children from Bogota, Colombia. The effects of correcting vitamin B-12 deficiency on educational outcomes and neurocognitive development of school children need to be determined in intervention studies.